Evaluating the Feasibility of a Statewide Collaboration to Improve Cardiac Rehabilitation Participation: THE MICHIGAN CARDIAC REHAB NETWORK. Issue 6 (13th November 2022) - Thompson, Michael P.; Yaser, Jessica M.; Forrest, Annemarie; Keteyian, Steven J.; Sukul, Devraj
Abstract : This study demonstrated the feasibility of a statewide collaboration of acute care hospitals and cardiac rehabilitation facilities centered around the goal of equitably improving cardiac rehabilitation enrollment for all eligible patients in Michigan, one that is supported by a diverse, multidisciplinary stakeholder group and is driven by performance-benchmarking data. Abstract : Purpose: Regional quality improvement collaboratives may provide one solution to improving cardiac rehabilitation (CR) participation through performance benchmarking and provider engagement. The objective of this study was to evaluate the feasibility of the Michigan Cardiac Rehab Network to improve CR participation. Methods: Multipayer claims data from the Michigan Value Collaborative were used to identify hospitals and CR facilities and assemble a multidisciplinary advisory group. Univariate analyses described participating hospital characteristics and hospital-level rates of CR performance across eligible conditions including enrollment within 1 yr, mean days to first CR visit, and mean number of CR visits within 1 yr. Three diverse CR facilities were chosen for virtual site visits to identify areas of success and barriers to improvement. Results: A total of 95 hospitals and 84 CR facilities were identified, with 48 hospitals (51%) providing interventional cardiology services and 33 (35%) providing cardiac surgical services. A 17-member multidisciplinary advisory group was assembled representing 13 institutions and diverse roles. Statewide CR enrollment across eligible admissions was 33.4%, with wide variation in CR performance measures across participating hospitals and eligible admissions. Virtual site visits revealed individual successes in improving CR participation but a variety of barriers to participation related to referrals, capacity and staffing constraints, and geographic and financial barriers. Conclusions: This study demonstrated the feasibility of creating a statewide collaboration of hospitals and CR facilities centered around the goal of equitably improving CR enrollment for all eligible patients in Michigan that is supported by a multidisciplinary advisory group and performance benchmarking.